NGAL: An Upcoming Biomarker of Interest - Khushbu Jasotani; Kiran Dahiya; Pragati Singh; Sushil Kumar; Keerti Gupta (Current Topics on Chemistry and Biochemistry Vol. 6, 2022)
Members of the lipocalin protein family are typically small secreted proteins. NGAL, or neutrophil gelatinase associated lipocalin, serves many important functions in the body. It has the potential to act as a biomarker for both diagnosis and prognosis for different diseases. In addition to renal diseases, NGAL participates in the pathogenesis of a number of other diseases, such as cardiovascular diseases, inflammatory disorders, cancer, diabetes, etc. In most disorders, its levels have been linked to disease severity. The main properties and functions of NGAL have been discussed in this chapter which will help in establishing its role in early diagnosis, evaluation of the severity, determining prognosis, and improving the management of various diseases.